2019
DOI: 10.1155/2019/3753485
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Mediate Hippocampal and Cortical Neuronal Injury Induced by Hepatic Ischemia-Reperfusion Injury through Activating Pyroptosis in Rats

Abstract: Background The neuronal injury and cognitive dysfunction after liver transplantation have severe effects on the prognosis and life quality of patients. Accumulating evidence suggests that both exosomes and pyroptosis could participate in hepatic ischemia-reperfusion injury (HIRI) and play key roles in neuronal death. However, the link between exosomes and neuronal pyroptosis in HIRI awaits further investigation. Methods After establishing the HIRI rat models, we primarily studied the role of pyroptosis in hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 73 publications
(78 reference statements)
0
51
0
Order By: Relevance
“…indicate that cerebral ischemia/reperfusion is involved in the canonical non-infectious pathway of pyroptosis in multiple cell types, including vascular endothelial cells, neurons, and astrocytes involves the canonical noninfectious pathway of pyroptosis [31][32][33]. However, to date, it is not known whether co-culturing OM-MSCs with microglia has a protective effect against either pyroptotic or apoptotic cell death during cerebral I/R injury.…”
Section: Agingmentioning
confidence: 99%
“…indicate that cerebral ischemia/reperfusion is involved in the canonical non-infectious pathway of pyroptosis in multiple cell types, including vascular endothelial cells, neurons, and astrocytes involves the canonical noninfectious pathway of pyroptosis [31][32][33]. However, to date, it is not known whether co-culturing OM-MSCs with microglia has a protective effect against either pyroptotic or apoptotic cell death during cerebral I/R injury.…”
Section: Agingmentioning
confidence: 99%
“…The top 10 GS genes in the key module, namely GUSBP11, KRT23, PLA2G7, IGLL3P, IGLJ3, S100A11, OSBPL3, CMTM7, IL18, CD3D, were selected as the hub genes, which were further confirmed significantly up‐regulation in an independent data set. It was previously reported that KRT23, 37 S100A11 38 and IL18 39 contributed to liver injury. Besides, the serum levels of these three proteins could be detected easily.…”
Section: Discussionmentioning
confidence: 92%
“…Pyroptosis, a specific pro-inflammatory programmed cell death, is characterized by the swelling and rupture of cells and the lysis and release of pro-inflammatory molecules ( Xing et al., 2020 ; Zheng and Li, 2020 ). Pyroptosis is considered an important factor in models of renal, hepatic and myocardial ischemia and reperfusion injury ( Wu et al., 2016 ; Qiu et al., 2017 ; Zhang et al., 2019 ). Consequently, we speculated that BA may downregulate pyroptosis in SCIRI.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis is a programmed inflammatory necrotizing cell death mediated by gasdermin D (GSDMD) ( Shi et al., 2017 ). Its main characteristic is the activation of the inflammasome, represented by NLRP3, which can recruit and activate the proteolytic enzyme caspase-1 leading to the cleavage of the pore-forming protein GSDMD and the maturation of the proinflammatory cytokines interleukin-1β (IL-1β) and IL18 ( Zhang et al., 2019 ). Studies have indicated that the production of reactive oxygen species (ROS) can activate the NLRP3 inflammasome ( Qiu et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%